Evaluation of a Multilingual Kindergarten Model in Slovenia: Insights from teachers, parents and children - Žefran, Mojca; Bratož, Silva; Rutar, Sonja (Neofilolog, 2025)
This paper presents an in-depth evaluation of a Multilingual Kindergarten Model (MU-KI Koper) developed in Slovenia aimed at integrating pluralistic approaches to language learning into early childhood education. The model activities were carried out over a period of nine months. The data were collected through focus group discussions with parents and in-service preschool teachers engaged in the implementation of the model, an online questionnaire for parents and through semi-structured interviews with the children (aged 5-6) involved in the model implementation. We explored the efficacy of the model by focusing on the following categories: the suitability and perception of effectiveness of the activities in meeting the needs of the pre-school curriculum in the area of developing multilingual competences, the children’s response to the programme, and the parents’ expectations and their feedback on meeting their expectations regarding the implementation of the model. The findings reveal that the Multilingual Kindergarten Model effectively supports children’s cognitive, linguistic and affective development through age- and developmentally-appropriate activities, while fostering early language awareness, positive attitudes towards languages and cultural curiosity.